Management Modalities of Pancreatic Cancer and Surgical Outcomes of Braun’s Anastomosis Addition in Whipple’s Procedure: A Single-center Prospective Study - Omara, Mohamed; Youssef, Elfatih; Doush , Dr.Wael (AL-Kindy College Medical Journal, 2024)
Background: Pancreatic cancer is an aggressive malignancy with high mortality rate. Many morbidities associated with Whipple’s procedure that endanger patients’ life which need updated surgical techniques to lower these morbidities. The aim of this study is to determine management modalities of pancreatic cancer and surgical outcomes of adding Braun’s jejunojejunostomy to Whipple’s procedure for reduction of postoperative risks in Sudanese patients to reach excellent surgical practice. Subjects and Methods: This is a prospective-cohort study conducted during the period between January 2022 and July 2023 at Ibn Sina specialized hospital, Khartoum, Sudan, on sixty-three patients diagnosed with resectable pancreatic cancer. Addition of Braun’s jejunojejunostomy to elective open Whipple’s surgery was performed. Results: Seventy-three percent of patients diagnosed with pancreatic cancer were males with the ratio (3:1). Patients’ distribution according to age ranged between 46 and 60 years representing (41.3%). The significant reported comorbidities that associated with PC were diabetes mellitus (30.2%) and businessmen (39.7%). Most of patients were lived in rural areas (57.1%). Abdominopelvic CT-scan revealed stage (II) of pancreatic cancer in (68.2%) of patients. The predominant morbidity after addition of Braun’s jejunojejunostomy was wound infections noticed in (17.5%) of patients. Moreover, other complications were categorized as follows: pulmonary infections in (6.35 %) of cases, postoperative diabetes mellitus in (4.76 %) of cases, entero-cutaneous fistula in (4.76 %) of cases, delayed gastric emptying in (3.17%) of cases, biliary leak in (3.17%) of cases, (3.17%) of cases, pancreatic fistula in one case (1.58%), gastric outlet obstruction in one case (1.58%) and postoperative GIT bleeding in one case (1.58%). Postoperative hospital stay of patients were ranged between 8-15 days for (66.7%) of cases. The mortality rate was zero. Conclusions: To reduce the rate of lethal surgical morbidities of Whipple’s procedure, we recommend addition of Braun’s jejunojejunostomy as useful technique. Moreover, it will potentially help in improving the quality of surgical practice and survival outcomes of patients who diagnosed with pancreatic cancer.